Conjugated polymer covalently modified graphene oxide quantum dots for ternary electronic memory devices. Issue 30 (20th July 2017) - Fan, Fei; Zhang, Bin; Cao, Yaming; Yang, Xutong; Gu, Junwei; Chen, Yu
Abstract : A novel arylamine-based polyazomethine covalently functionalized graphene oxide quantum dots (TPAPAM-GOQDs), which exhibited nonvolatile ternary memory effect with an OFF : ON-1 : ON-2 current ratio of 1 : 60 : 3000, was synthesized. Abstract : Zero dimensional graphene oxide (GO) quantum dots (GOQDs) have been expected to play an important role in the development of new memory materials. When the size of GO was reduced to that of GOQDs, both the electron affinity and ionization potential of GO were found to be decreased, and this was followed by the elevation of lowest energy unoccupied molecular orbital (LUMO) energy level. This implies that the electron withdrawing ability of GOQDs is weaker than that of GO. In this work, a novel arylamine-based polyazomethine covalently functionalized graphene oxide quantum dots (TPAPAM-GOQDs), which was synthesized using an amidation reaction, was for the first time used to fabricate a ternary memory device with a configuration of gold/TPAPAM-GOQDs/indium tin oxide. The current ratio of OFF : ON-1 : ON-2 was found to be 1 : 60 : 3000. Its conductive nature was also revealed using an in situ conductive atomic force microscopy technique. This memory device could potentially increase the memory capacity of the device from the conventional 2 n to 3 n when compared to binary memory devices.